PERÍODOS DE INTERFERÊNCIA E CONTROLE QUÍMICO DAS PLANTAS DANINHAS NA CULTURA DA CEBOLA TRANSPLANTADA EM DIFERENTES POPULAÇÕES - Souza, João Igor de (2014)
The work was conducted with the objective of determining the critical periods for weed competition with weeds (CPWC) and management periods of weed community in onion crop transplanted in three distinct densities of Mercosul Crioula genotype. Three experiments were carried out in field conditions at Guarapuava County, Paraná State, during 2012 and 2013 agricultural years, at Universidade Estadual do Centro-Oeste - UNICENTRO. Treatments were set up in randomized complete blocks experimental design. In experiment 1, treatments were constituted by periods of weed coexistence at 14, 28, 56, 112 and 168 days after seedlings transplant (DAST), with five repetitions. In experiments 2 and 3, treatments were constituted by unique applications (2012 agricultural year) and sequential process (2013 agricultural year) of narrow leaf and broad leaf herbicides: ioxynil-octanoato/ fenoxaprop-p-ethyl; flumioxazin/ fenoxaprop-p-ethyl; oxadiazon; bentazon/ fenoxaprop-p-ethyl; and two checks maintained with and without infestation, by using three densities of onion plants (0,6, 0,8 and 1,0 million plants ha?¹). From adjusted models it was not observed viability in the increase of plantation density as a new practical that may favor the necessity reduction of weeds management. Onion plants transplanted in August, 2012 and July, 2013 presented CPWC, respectively, of 23 to 76 and 21 to the 120 DAST, when it was objectified commercial bulbs yield, and of 20 to 55 and 26 to the 112 DAST, for total bulbs yield. Control with a unique delayed application of narrow leaf and all broad leaf herbicides at 30/35 DAST was inefficient for adequate weeds management, independently of onion crop density, as well as insufficient for guaranteeing adequate production of commercial and/or total onion bulbs in 2012 agricultural year. Weeds control through delayed application and in sequential of broad leaf herbicides in 2013 agricultural year, even being satisfactory for some species, did not provide adequate production of commercial and/or total onion bulbs.